Consequences of Sclera-fixated Intraocular Lens (SFIOL) Implantation after 1 Year Follow Up (Journal of National Institute of Ophthalmology, 2022)
Purpose: To evaluate the consequences of sclera-fixated intraocular lens (SFIOL) after one year of implantation surgery.Methods: This observational study was conducted among 50 patients at the National Institute of Ophthalmology and Hospital (NIOH), Dhaka, from June 2021 to December 2021. The study population was taken among patients whose SFIOL surgeries were performed in the Department of vitreo retina. The sampling method was purposive sampling. Variables were age, gender, best corrected visual acuity (BCVA), lens status, etiological factor, history of pars plana vitrectomy, and post-operative complications. All examinations were done accordingly, and collected data were correctly recorded. Ethical principles were followed.Results: The mean age was 54±18.3 years where 72% of cases were male. Aphakia was present in 64% of patients, 14% of patients had pseudophakia, and 22% were phakic. Among the patients, 78% had a history of complications due to cataract surgery and 18% suffered from trauma. Both anterior and pars plana vitrectomy were done to 46% of patients, and 54% had been treated only with anterior vitrectomy. In this study, mean BCVA was 1.4±0.5 during admission, 0.8±0.3 during discharge, 0.5±0.3 after one month and 0.3±0.2 after one year. After one year, BCVA significantly decreased from admission (p=0.001). Post-operative complications were found in 6% of cases.Conclusion: After SFIOL implantation, significant visual improvement appeared. It's a sight-saving process that gives patients better visual acuity.J. Natl. Inst. Ophthalmol. 2022; 5(2):16-20